2021
DOI: 10.5194/jsss-10-127-2021
|View full text |Cite
|
Sign up to set email alerts
|

A classification technique of civil objects by artificial neural networks using estimation of entropy on synthetic aperture radar images

Abstract: Abstract. The article discusses the method for the classification of non-moving group objects for information received from unmanned aerial vehicles (UAVs) by synthetic aperture radar (SAR). A theoretical approach to analysis of group objects can be estimated by cross-entropy using a naive Bayesian classifier. The entropy of target spots on SAR images revaluates depending on the altitude and aspect angle of a UAV. The paper shows that classification of the target for three classes able to predict with fair acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Having obtained the data, it became possible to develop a supervised learning algorithm [ 42 , 43 ]. The results showed that the “Fine tree” algorithm with Gini diversity index separability criterion with 68.1% of correct results was more effective for linearly polarized wave ( Figure 9 ).…”
Section: Supervised Learning For Polarimetric Recognitionmentioning
confidence: 99%
“…Having obtained the data, it became possible to develop a supervised learning algorithm [ 42 , 43 ]. The results showed that the “Fine tree” algorithm with Gini diversity index separability criterion with 68.1% of correct results was more effective for linearly polarized wave ( Figure 9 ).…”
Section: Supervised Learning For Polarimetric Recognitionmentioning
confidence: 99%